MAIN CHARACTER IN KUNG FU PANDA MOVIE BY EITHAN REIFF AND CYROUS VORIS - Wibawa, Pande Made Satria (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTThis paper is entitled "The Main Character in the Movie Kung Fu Panda byEithanReiff and CyrousVoris". The research data was taken from a film entitled Kung FuPanda. Data collection was carried out through observation methods by watching, reading andtaking notes. Then categorized based on theory. The collected and classified data were analyzedqualitatively and descriptively based on the characterization theory proposed by Kenney(1966), Three Dimensional Aspects proposed by Lajos Egri (1987). The results of the analysis,it is known that Po Ping is the main character in the film. The author uses three-dimensionalaspect of the main character's based on theory proposed by Lajos Egri (1987) which arephysiology, psychology, and sociological aspect. From a psychological point of view the maincharacter shows that he does not give up easily and tries his best to fulfill his destiny as a dragonwarrior, from a physiological point of view the main character is shown by Po as a big fatpanda. From a sociological point of view, the main character is the son of a ramen noodle sellerand become a dragon warrior.Keywords: Character, Characterization, Method of Characterization, Three Dimensions ofCharactersABSTRAKTulisan ini berjudul "Tokoh Utama dalam Film Kung Fu Panda oleh Eithan Reiff danCyrousVoris". Data penelitian diambil dari film yang berjudul Kung Fu Panda. Pengumpulandata dilakukan melalui metode observasi dengan menonton, membaca dan mencatat.Kemudian dikategorikan berdasarkan teori. Data yang terkumpul dan terklasifikasi dianalisissecara kualitatif dan deskriptif berdasarkan teori karakterisasi yang dikemukakan oleh Kenney(1966), Aspek Tiga Dimensi yang dikemukakan oleh Lajos Egri (1987). Hasil analisis diketahuibahwa Po Ping adalah pemeran utama dalam film tersebut. Penulis menggunakan aspek tigadimensi dari tokoh utama berdasarkan teori yang dikemukakan oleh Lajos Egri (1987) yaituaspek fisiologi, psikologi, dan aspek sosiologis. Dari segi psikologis tokoh utama menunjukkanbahwa ia tidak mudah menyerah dan berusaha sekuat tenaga untuk memenuhi takdirnyasebagai seorang prajurit naga, dari segi fisiologis tokoh utama diperlihatkan oleh Po sebagaiseekor panda gemuk besar. Dari segi sosiologis, tokoh utamanya adalah anak seorang penjualmie ramen dan menjadi seorang pendekar naga.Kata Kunci: Karakter, Karakterisasi, Metode Karakterisasi, Tiga Dimensional AspekKarakter.